Seafood authenticity and traceability : a DNA-based pespective - Naaum, Amanda; Hanner, Robert (Academic Press is an imprint of Elsevier, 2016)
Seafood Authenticity and Traceability: a DNA-based Pespective is a concise reference showcasing the latest developments in the field. Written for those in food authenticity who may not have a technical molecular biology background, the book covers methods used for DNA analysis and an overview of their applications in fish and seafood, also providing reviews of the technology and processes for each method. It offers a practical and succinct overview of the relationship between accurate identification, traceability, sustainability, and safety of seafood, including an overview of the supply chain and the industry's need for improved traceability. Presents current and future perspectives in the emerging field of traceability, including solid coverage of DNA analysis for origin detectionIncludes molecular authentication tools to improve species identification throughout the seafood industryProvides reviews of the technology and processes for each DNA analysis methodOffers a comprehensive overview for those in food authenticity who may not have an in-depth molecular biology background.